Simultaneous surgical management of a giant tuberculum sellae meningioma and pregnancy-related complications: a case report and literature review - Tleubergenov, Muratbek A.; Ryskeldiyev, Nurzhan A.; Baymukhanov, Dauren S.; Zhamoldin, Daniyar K.; Akshulakov, Serik; Doskaliyev, Aidos (Frontiers in Oncology, 2025)
Meningiomas, tumors arising from the brain and spinal cord membranes, pose a unique challenge when diagnosed during pregnancy. Their growth can accelerate due to hormonal and hemodynamic changes, necessitating careful clinical evaluation to balance maternal and fetal risks. This article presents a case report and literature review on the successful simultaneous management of a giant tuberculum sellae meningioma and pregnancy-related complications in a 35-year-old woman at 38 weeks of gestation. The patient experienced progressive visual deterioration, prompting an emergency surgical intervention. A multidisciplinary team performed a simultaneous pterional craniotomy with microsurgical tumor resection alongside a cesarean section, ensuring optimal outcomes for both mother and child. Postoperative results demonstrated significant improvement in the patient’s vision and neurological function, with a healthy neonate delivered without complications. The histopathological examination confirmed an atypical meningioma (WHO Grade II), reinforcing the need for long-term follow-up and oncological assessment. In addition to the case report, this study reviews the existing literature on meningiomas during pregnancy, focusing on hormonal influences, diagnostic challenges, and treatment strategies. We discuss the role of multimodal imaging, including MRI without contrast, as a primary diagnostic tool and evaluate the risks associated with different treatment approaches. The review highlights the importance of timely surgical intervention, particularly in cases of rapidly growing or symptomatic tumors, and underscores the feasibility of simultaneous neurosurgical and obstetric procedures when clinically indicated. This review emphasizes the necessity of a multidisciplinary approach involving neurosurgeons, obstetricians, anesthesiologists, and neonatologists to optimize both maternal and fetal outcomes. By combining clinical expertise with a thorough literature analysis, we provide valuable insights into the management of intracranial tumors in pregnancy, contributing to the development of treatment protocols for such complex cases.